Kripkenstein's Paradox - Picazo, Gustavo (Análisis. Revista de investigación filosófica, 2016)
In this note I present a solution to Kripkenstein’s paradox, based on a very simple argument: (1) language and rule-following are empirical phenomena; (2) no case has been described, in real life, of a person who behaves as Wittgenstein’s or Kripke’s fictional character; (3) therefore, the discussion of such a case is completely devoid of interest. I lay out the example of a ‘Kripkensteinian apple’, which has a normal weight on even days and is weightless on odd days, in order to highlight the contrast between a genuinely empirical perspective, such as that of physics, and the logical-analytical perspective, under which Kripkenstein’s paradox has attracted so much attention.